The role of sleep quality and fatigue on the benefits of an interdisciplinary treatment for adults with chronic pain. - De la Vega, Rocío; Racine, Mélanie; Castarlenas, Elena; Solé, Ester; Roy, Rubén; Jensen, Mark P.; Miró, Jordi; Cane, Douglas (Wiley, 2018)
Background: Interdisciplinary chronic pain treatment is effective for reducing pain intensity and pain-related disability, and for improving psychological function. However, the mechanisms that underlie these treatment-related benefits are not yet well understood. Sleep problems and fatigue are modifiable factors often comorbid with chronic pain. The goal of this study was to evaluate the role that changes in sleep quality and fatigue might have on the benefits of an interdisciplinary chronic pain treatment. Methods: A total of 125 adults with chronic pain participated in a 4-week interdisciplinary pain management program. Measures of depression, sleep disturbance, fatigue, pain intensity, and physical function were administered at pre- and post-treatment. Three regression analyses were conducted to evaluate the contribution of pre- to post-treatment improvements in fatigue and sleep disturbance to the pre- to post-treatment improvements in pain intensity, disability, and depression, while controlling for demographic characteristics (age and sex) and pain intensity. Results: Changes in fatigue and sleep disturbance made independent and significant contributions to the prediction of treatment-related benefits in pain intensity; improvements in depressive symptoms were predicted by improvements in fatigue, and improvements in disability were only predicted by pre-treatment and pre- to post-treatment decreases in pain intensity (one of the control variables). Conclusions: In addition to sleep, fatigue emerged as a key potential mechanism of multidisciplinary chronic pain treatment- related improvements, suggesting that interventions including elements that effectively target sleep and fatigue may enhance the efficacy of interdisciplinary chronic pain programs. This possibility should be evaluated in future research.
Es una versión preprint. https://openpolicyfinder.jisc.ac.uk/id/publication/2564
Keywords: Dolor crónico; Terapia cognitiva; Fatiga; Sueño; Depresión mental; Chronic pain; Cognitive behavioral therapy; Sleep; Fatigue; Depression